Facultad de Ciencias Administrativas trabajó en taller de Aseguramiento de la Calidad - García García, Mariana (2023)
The Faculty of Administrative Sciences, Business Management and Informatics of the UEB, through planning by the Dean's Office, appointed Lic. Marcelo Barriga, delegate by FACAGEI to the Internal Quality Assurance Directorate of the State University of Bolívar, coordinated a 2-day workshop for fellow faculty members on the topic: Quality Assurance, which was accompanied by the MBA. Jorge Goyes, director of Planning and Quality Assurance